Highly conductive and scalable Ti3C2Tx-coated fabrics for efficient electromagnetic interference shielding. (15th April 2021) - Uzun, Simge; Han, Meikang; Strobel, Christina J.; Hantanasirisakul, Kanit; Goad, Adam; Dion, Genevieve; Gogotsi, Yury
Abstract: As an increasing number of wireless devices are introduced to our daily lives, long-term environmentally stable conductive fabrics that can shield against electromagnetic radiation are increasingly desired. Herein, conventional cotton and linen fabrics were dip-coated in additive-free, aqueous Ti3 C2 T x MXene dyes, which consist of only two-dimensional Ti3 C2 T x flakes dispersed in water, to fabricate highly conductive fabrics for electromagnetic interference (EMI) shielding. Ti3 C2 T x loading and electrical conductivity of the fabrics increased with the number of dip-coating cycles. After only 4 dip-coating cycles, EMI shielding effectiveness (SE) of Ti3 C2 T x -coated (<15 wt%) cotton and linen fabrics reached ∼40 dB over the X-band range. After 24 dip-coating cycles, the total EMI SE increased to ∼80 dB for Ti3 C2 T x -coated cotton (54 wt%) and linen (48 wt%) fabrics, which is higher than commercial metal-based conductive fabrics tested in this study. The average EMI SE performance of Ti3 C2 T x -coated cotton and linen fabrics only decreased by ∼8% and ∼13%, respectively, after storage under ambient conditions for two years. This work suggests an attractive alternative to current metal-based conductive dyes and provides valuable insights into the development of environmentally stable wearable EMI shielding materials. Graphical abstract: Image 1